Flexibility in Management: Applying the 'Anything Goes' Principle to Innovation and Decision Making - Wulandari, Sri (Garuda Prestasi Nusantara Consulting, 2024)
Flexibility in organizations is an increasingly important principle in dealing with rapidly changing market dynamics. This study aims to explore how the application of flexibility in decision-making and innovation, by relating to the concept of methodological freedom developed by Paul Feyerabend, can strengthen organizational performance and resilience. Using case studies from several leading companies such as Google, Netflix, Amazon, Zara, and Tesla, the study analyzes how freedom to choose different methodological and experimental approaches can drive innovation, improve responsiveness to change, and provide a sustainable competitive advantage. Organizations that implement flexibility in their operational structure and managerial strategy show improvements in creativity, resilience to uncertainty, and adaptability to external changes. However, the main challenge faced is maintaining a balance between individual freedom and a clear organizational structure. Leadership that supports experimentation and views failure as part of the learning process has proven to be an important factor in creating an innovative culture. This research provides valuable insights for managerial practitioners and academics regarding the importance of implementing flexibility to achieve competitive advantage in organizations. Keywords: Flexibility, Innovation, Decision Making, Methodological Freedom, Anything Goes, Organization, Leadership, Creativity, Resilience, Innovative Culture